Project 2B. Shapes into planes / Nur Hureen Fatihah Hafiz Khoo - Hafiz Khoo, Nur Hureen Fatihah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The basic shapes found from the shapes of terabai and the movement of circle and triangle which are then extracted and used to make transformation using various size and solid and void in plans. The interplay of repetition of planes in different sizes create a natural rhythm and smooth movement into the patterns. Triadic colors of green and violet as dominant color to create a sense of calm and serene inspired from the movement of the Bidayuh people while turning and swaying their hand with this shield.